2010
DOI: 10.1136/emj.2010.095885
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute myocardial infarction resulting in sudden death outside the hospital

Abstract: The estimated mortality of AMI appears to be 35% in this population. This figure suggests that significant improvement in the treatment of out-of-hospital cardiac arrest is still necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Linkage across all data sources was used to improve case ascertainment because 25% to 50% of cardiovascular events are not recorded in at least 1 of the 3 sources. [14][15][16] The first cardiovascular event after the diagnosis of gout was used to ascertain case status as lifestyle changes after such an event may be associated with fewer subsequent gout flares. 17…”
Section: Nested Case-control Studymentioning
confidence: 99%
“…Linkage across all data sources was used to improve case ascertainment because 25% to 50% of cardiovascular events are not recorded in at least 1 of the 3 sources. [14][15][16] The first cardiovascular event after the diagnosis of gout was used to ascertain case status as lifestyle changes after such an event may be associated with fewer subsequent gout flares. 17…”
Section: Nested Case-control Studymentioning
confidence: 99%
“…The most common cause of sudden, unexpected, natural deaths in adults is arteriosclerotic cardiovascular disease, which accounts for as many as 34-55% of all such deaths (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is encouraged by the small proportion of present physicians (5–6%) and the high frequency of 36% among prehospital fatal cases with no witness for testifying the out-of-hospital deaths. A prospective study in France estimated that 35% out-of-hospital sudden deaths were due to acute MI 16 . The Finnish Genetic Study of Arrhythmic Events 17 found an even higher proportion of sudden deaths in relation to CHD.…”
Section: Discussionmentioning
confidence: 99%